2019
DOI: 10.1097/jpa.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Online Training Modules and Virtual Patients on First-Year Physician Assistant Students' Confidence Levels

Abstract: Purpose Pilot study assessing impact of virtual patients (VPs) and online modules on first-year physician assistant (PA) student confidence in documentation performance. Methods Five VP cases (head, eyes, ears, nose, and throat; musculoskeletal; abdominal; neurological; and comprehensive history and physical examination) and one module (cardiac sounds) were implemented to complement the core PA curriculum. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Similar to our findings, a prior study assessing virtual methods using virtual patients for HT training showed improvements in global performance, interviewing technique, and logical sequence [ 25 ]. In line with this study, another report also revealed that virtual HT significantly increased students’ confidence to two-thirds of nearly half of the respondents [ 26 ]. Moreover, a previous study also showed that virtual auscultation courses using interactive case-based webinars were practical, interactive, and well-received by the students [ 27 ].…”
Section: Discussionsupporting
confidence: 84%
“…Similar to our findings, a prior study assessing virtual methods using virtual patients for HT training showed improvements in global performance, interviewing technique, and logical sequence [ 25 ]. In line with this study, another report also revealed that virtual HT significantly increased students’ confidence to two-thirds of nearly half of the respondents [ 26 ]. Moreover, a previous study also showed that virtual auscultation courses using interactive case-based webinars were practical, interactive, and well-received by the students [ 27 ].…”
Section: Discussionsupporting
confidence: 84%